Commentary on true and false religion - Zwingli, Ulrich, 1484-1531; Jackson, Samuel Macauley 1851-1912; Heller, Clarence Nevin (Philadelphia, PA Heidelberg, 1929)
Includes index.
Translation of De vera falsa religione commentarius. Reprint (1981) by Labyrinth Press, Durham, NC. Originally published : The Latin works and the correspondence of Huldreich Zwingli, v. 3, issued under title : The Latin works of Huldreich Zwingli.
Keywords: Theology -- addresses, essays, lectures